A two-year retrospective study of multidrug-resistant Acinetobacter baumannii respiratory infections in critically Ill patients: Clinical and microbiological findings - Taghreed A. Hafiz; Shahad S. Alghamdi; Murad A. Mubaraki; Shymaa S.M. Alghamdi; Abdulwahab Alothaybi; Esraa Aldawood; Fawziah Alotaibi (Elsevier, 2023)
Background: Acinetobacter baumannii infection is a serious public health problem because it is highly resistant to antimicrobial therapy and causes a high fatality rate in critically ill patients. The aim of the study is to examine the demographics, microbiological findings, clinical presentation, and outcomes of multi-drug-resistant Acinetobacter baumannii respiratory infections in adult ICU intubated patients during COVID-19 pandemic. Methods: This study included 115 mechanically ventilated adult ICU patients who had multi-drug-resistant Acinetobacter baumannii retrieved from respiratory samples during the COVID-19 pandemic in Albaha, Saudi Arabia. The information was obtained from medical and laboratory files. Univariate analysis was used to compare gender, COVID-19 infection, and outcomes. Results: The rate of Acinetobacter baumanni respiratory infections among adult ICU patients was 6.2 %. Almost 93 % developed ventilator-associated pneumonia, and five of them developed bacteremia. The isolates had significant antibiotic resistance patterns, of which 3 % were pandrug-resistant bacteria. The death rate was 74 %, with major risk factors including sepsis, septic shock, VAP, liver diseases, and the use of inappropriate antibiotic therapy that lacked both colistin and tigecycline. Patients with COVID-19 coinfection had worse outcomes compared to non-COVID-19 patients. Conclusions: The identification of MDR-AB as a threat highlights the importance of surveillance studies in this region.